Green construction project management and cost oversight - Kubba, Sam. 4 0 16; 5 (Amsterdam : Architectural Press/Elsevier, 2010)
A guide to environmentally-friendly and sustainable construction financing and cost management, providing practical guidelines to prepare green building documentation, case studies based on the author's real-life experiences, and sample forms, reports, letters, and agreements.
Green and sustainability defined -- Elements of green design and construction -- Green project requirements and strategies -- Green construction cost monitoring -- How the consultant functions in the requisition process -- Choosing materials and products -- Project cost breakdown -- Green design and construction economics -- Understanding specifications -- Litigation and liability issues -- Green project commissioning -- Green business development.
Includes bibliographical references and index.
Adult;Adult.
Keywords: 2 -- 0; 6; Cost control. -- Sustainable construction.;Building -- 20; 20; 2